The impact of share-based payment plans on the performance of brazilian companies before and during the Covid-19 pandemic - Oliveira, Danielle de Pauli; Carmo, Carlos Henrique Silva do; Silva, Lívia Janaína; Machado, Lúcio de Souza (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Purpose: The study investigated the effects of Share-Based Payment Plans (SBP) on the performance of Brazilian companies before and during the period of the Covid-19 pandemic. Methodology: The sample comprised 186 companies listed on B3 in the Novo Mercado, Level 1 and 2 segments, between 2018 and 2021. Four performance indicators (EPS, ROA, ROE, and ROS) and three PBA metrics (Adoption, Type of Settlement, and Type of Exercise Price) were used. Regressions were estimated with panel data and random effects. Results: The results indicate that, in the pre-pandemic period, stock-based payment (SBP) contracts with exercise prices higher than the stock value at the contract date (out of the money) had a positive effect on organizational performance, as measured by return on assets (ROA) and return on sales (ROS), suggesting that only plans with more demanding exercise price conditions are associated with performance improvements. However, during the pandemic, a negative relationship was observed between plan adoption and ROA, as well as between the settlement type and earnings per share (EPS), indicating that the use of SBP may increase risk-taking and negatively impact organizational performance in times of financial stress. Furthermore, the higher risk introduced by SBP results in more significant performance declines during recessive periods, making it essential to implement stricter monitoring of managerial actions during financial crises. Contributions of the Study: The study contributes theoretically by advancing the understanding of the contingency of financial incentives in different economic scenarios based on Agency Theory. From a practical perspective, it underscores the importance of structuring stock option plans with flexibility, such as conditional and adjustable exercise prices for periods of financial stress, and strengthening governance. In the social aspect, it underscores the need for sustainable compensation policies that balance executive incentives with the protection of investors and stakeholders.